A Meta-Analysis of Adenosine A2A Receptor Antagonists on Levodopa-Induced Dyskinesia In Vivo - Wang, Wen-Wen; Zhang, Man-Man; Zhang, Xing-Ru; Zhang, Zeng-Rui; Chen, Jie; Feng, Liang; Xie, Cheng-Long (Frontiers in Neurology, 2017)
Background: Long-term use of L-dopa (Levodopa) is inevitably complicated with highly disabling fluctuations and drug-induced dyskinesias, which pose major challenges to the existing drug therapy of Parkinson’s disease (PD). Methods: In this study, we conducted a systematic review and meta-analysis to assess the efficacy of A2A receptor antagonists on reducing L-dopa-induced dyskinesias (LID). Results; Nine studies with a total of 152 animals were included in this meta-analysis. Total AIM (abnormal involuntary movements) score, locomotor activity and motor disability were reported as a outcome measure in 5, 5 and 3 studies, respectively. Combined standardized mean difference (SMD) estimates were calculated using a random-effects model. We pooled the whole data and found that, when compared to L-dopa alone, A2A receptor antagonists plus L-dopa treatment showed no effect on locomotor activity (SMD -0.00, 95% CI: -2.52 to 2.52, p=1.0), superiority in improvement of motor disability (SMD -5.06, 95% CI: -9.25 to -0.87, p=0.02) and more effective in control of abnormal involuntary movements (SMD -1.82, 95% CI: -3.38 to -0.25, p=0.02). Conclusions: To sum up，these results demonstrated that A2A receptor antagonists appear to have efﬁcacy in animal models of LID. However, large randomized clinical trials testing the effects of A2A receptor antagonists in LID patients are always warranted.